2008
DOI: 10.1109/tmag.2007.911036
|View full text |Cite
|
Sign up to set email alerts
|

Low Flying-Height Slider With High Thermal Actuation Efficiency and Small Flying-Height Modulation Caused by Disk Waviness

Abstract: To sustain an ultra-low and stable flying height (FH) is crucial for achieving high areal densities in magnetic recording. Recently, a new method called thermal flying height control (TFC) has been introduced to the latest generations of disk drives for precise control of sliderdisk spacing. It is noted that the TFC technique is able to eliminate almost all static FH loss, but is unable to circumvent dynamic FH loss such as flying height modulation (FHM) due to disk waviness. It is therefore advantageous to ha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
0

Year Published

2008
2008
2014
2014

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 34 publications
(16 citation statements)
references
References 8 publications
0
16
0
Order By: Relevance
“…Figure 1 shows the diagram of models used in the study. Liu et al (2008) gave a detailed description of this coupled-field analysis method.…”
Section: Numerical Methods and Modelsmentioning
confidence: 99%
“…Figure 1 shows the diagram of models used in the study. Liu et al (2008) gave a detailed description of this coupled-field analysis method.…”
Section: Numerical Methods and Modelsmentioning
confidence: 99%
“…Lower positive pressure of design B at a magnetic head therefore improves TFC efficiency. As one approach to improving TFC efficiency by ABS design, a groove structure around the magnetic head has been proposed [14,15]. To investigate the effect of TFC actuation on change in head-disk clearance at high altitude, we evaluated two ABS designs with different TFC efficiencies.…”
Section: Evaluated Samplesmentioning
confidence: 99%
“…In order to increase the efficiency of thermal flying height control sliders it is important to optimize the air bearing design of the air bearing surface (ABS) of the slider. Juang and Bogy (2007) and Liu et al (2008) found that a small isolated air bearing trailing pad supporting the read/ write element of the slider improves the thermal actuation efficiency of the TFC slider since it generates little air bearing pressure. A pad structure featuring trenches was proposed by Gonzaga and Liu (2009).…”
Section: Introductionmentioning
confidence: 99%